The perceptions of student teachers’ on student-centred learning - Shee, Mei Ling (2019)
This study examines the perceptions of student teachers on student-centred learning (SCL) after their teaching practicum in Singapore. Qualitative interviews were conducted with 15 student teachers. Using thematic analysis, 12 themes were elicited and categorised under four theme dimensions of student teachers’ perceptions on SCL. Findings revealed that student teachers have a diverse and comprehensive understanding of SCL. Student teachers recognised the use and benefits of SCL. However, they faced challenges in time constraints during lesson preparation, considerations for students’ profile, lesson implementation and curricular expectations. Therefore, support needs to be in place for student teachers to design, enact and manage SCL classrooms. Social support and informational resources are two important resources which can be reinforced during teacher education and in schools to encourage SCL implementation.